2022
DOI: 10.1021/acs.jafc.2c02654
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Polyphenols Alleviate Autoimmune Liver Disease by Mediating the Intestinal Microenvironment: Challenges and Hopes

Abstract: Autoimmune liver disease is a chronic liver disease caused by an overactive immune response in the liver that imposes a significant health and economic cost on society. Due to the side effects of existing medicinal medications, there is a trend toward seeking natural bioactive compounds as dietary supplements. Currently, dietary polyphenols have been proven to have the ability to mediate gut−liver immunity and control autoimmune liver disease through modulating the intestinal microenvironment. Based on the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 208 publications
0
4
0
Order By: Relevance
“…All cells in the tumor microenvironment are regulated by the NF-κB signaling pathway and influence the onset and progression of inflammation and cancer . It has been suggested that dietary anthocyanins may activate enteric nutrient sensors, including AMPK, and thereby directly inhibits the expression of the mTOR signaling pathway in dendritic cells, up-regulates heme oxygenase-1 (HO-1), and restrains hypoxia-inducible factor-1α (HIF-1α) . In addition, AMPK is related to the up-regulation of caudal-related homeobox transcriptional factor (CDX2), an intestinal-specific transcription factor that induces differentiation of epithelial cell, regulates genes in tight junction complexes, and controls intestinal inflammation .…”
Section: Mechanisms Underlying the Effects Of Anthocyaninsmentioning
confidence: 99%
See 1 more Smart Citation
“…All cells in the tumor microenvironment are regulated by the NF-κB signaling pathway and influence the onset and progression of inflammation and cancer . It has been suggested that dietary anthocyanins may activate enteric nutrient sensors, including AMPK, and thereby directly inhibits the expression of the mTOR signaling pathway in dendritic cells, up-regulates heme oxygenase-1 (HO-1), and restrains hypoxia-inducible factor-1α (HIF-1α) . In addition, AMPK is related to the up-regulation of caudal-related homeobox transcriptional factor (CDX2), an intestinal-specific transcription factor that induces differentiation of epithelial cell, regulates genes in tight junction complexes, and controls intestinal inflammation .…”
Section: Mechanisms Underlying the Effects Of Anthocyaninsmentioning
confidence: 99%
“…82 It has been suggested that dietary anthocyanins may activate enteric nutrient sensors, including AMPK, and thereby directly inhibits the expression of the mTOR signaling pathway in dendritic cells, up-regulates heme oxygenase-1 (HO-1), and restrains hypoxia-inducible factor-1α (HIF-1α). 83 In addition, AMPK is related to the up-regulation of caudal-related homeobox transcriptional factor (CDX2), an intestinal-specific transcription factor that induces differentiation of epithelial cell, regulates genes in tight junction complexes, and controls intestinal inflammation. 23 Meanwhile, anthocyanins appear to inhibit the Akt-mediated transcription factor NF-κB, which has anti-inflammatory effects by inhibiting NF-κB, adjusting phosphorylation of I-kappa-B-alpha (IκBα), and reducing the gene expression of pro-inflammatory cytokines such as TNF-α, IFN-γ, and IL.…”
Section: Preservation Of the Intestinal Epithelial Barrier Functionmentioning
confidence: 99%
“…The structural and functional features of the gastrointestinal tract render the organoid vulnerable to be an active inflammatory nidus in which host immune homeostasis is disturbed and inflammatory stresses are sustained with sufficient inflammation strength to perpetuate autoimmune responses in remote organ systems ( 163 , 164 ). In this process, probiotic commensal microbe-derived metabolites play important roles in maintaining epithelial integrity, regulating host immune responses, and modulating autoimmunity ( 177 , 178 , 193 196 ). An inadequate dietary supply can induce gut dysbiosis and immune dysregulation and affect epithelial repair function ( 197 200 ).…”
Section: Contribution Of Inflammatory Stressors To Autoimmune Diseasesmentioning
confidence: 99%
“…It seems that polyphenols can change the intestinal microecology, affect the total number of beneficial bacteria in the intestine, and bring positive intestinal health benefits [ 162 ]. It is reported that dietary polyphenols can treat liver immune diseases [ 163 ], nonalcoholic fatty hepatitis, nonalcoholic fatty liver disease and other related liver diseases by regulating intestinal microorganisms [ 164 ]. Because inflammation is accompanied by various stages of liver fibrosis, polyphenols can stimulate Firmicutes phylum , Bifidobacterium spp., Akkermansia spp., Roseburia spp.…”
Section: Dietary Polyphenols Affect Gut Microbiota Composition In Liv...mentioning
confidence: 99%